Respon Pertumbuhan Bibit Sengon Buto (Enterolobium cyclocarpum Griseb) Pada Media Tailing PT Antam Pongkor Dengan Penambahan Arang Batok Kelapa Dan Bokashi Pupuk Kandang - Basuki Wasis; Isminanda Alkautsar (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
Tailing is one of waste which is produce from gold mining activity and it’s contain little of nutrient. The one of way for manage tailing is revegetation of forest or tailing, the addition of coconut shell charcoal with bokashi manure on seedling Sengon Buto (Enterolobium cyclocarpum Griseb.) is one of species that have recommended for developing on post mining land revegetation with cheaper cost and also have good prospect and have high adaptability on various kinds of soil. The giving of coconut shell charcoal with dosage 0% (A0); 2,5% (A1); 5% (A2); 7,5% (A3); and 10% (A4) and for bokashi manure with dosage 0 g (B0); 20 g (B1); 40 (B2); and 60 g (B3) can helping the growth of Sengon Buto seedlings on tailing, this experiment is also have impact on both growing directly and increasing the nutrient of tailing. The highest of grow up of plant was found in A4B3 (adding of coconut shell charcoal with concentration 10% and bokashi manure with dosage 60 g into the tailing media) can increase significantly the growth of Sengon Buto seedlings and able to improve nutrient availability in the tailing. This implies that add of coconut shell charcoal and bokashi manure can fixing the chemist charateristic on the tailing media, and can impact on improvement of nutrient containing for the plant. Key words: bokashi manure, coconut shell charcoal, Sengon Buto, tailing